Integrative-Interconnective Approach in Islamic Studies (Crtical Studies on M. Amin Abdullah’s Thought) - Laila Ngindana Zulfa (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
M. Amin Abdullah was born in Pati, Central Java, on  July 28, 1953.  The Academic Anxiety  was experienced by Amin Abdullah is a dichotomy between religion and science education, human behavior is not as it should, and the global crisis that hit in the current era . He took the theory of Muhammad Abid al-Jabri as knives analysis to explain the Islamic epistemology  about Bayani’s, Burhani’s, and 'Irfani’s epistemology. And give attention to the philosophical approach wich it had been initiated by Fazlur Rahman  in order to try to integrate between kalam and philosophy. He divided the scientific form of Islam into 3 models: Single Entity, Isolated Entity, and interconected Entity. The Three-dimensional scientific development intend to bring back the modern sciences with  Islamic sciences  (integrated-interconned). The third form was being the cornerstone to develop an integrated-interconnected approach in relation to the scientific development of academic.  This wide approach is essentially just wanted to show that among the various fields of science actually interconnected, as targeted by the entire scientific disciplines is the reality of the universe which  is the same, only the dimensions and the focus of attention is seen by each scientific disciplines are different. Keywords: Scientific Models, Integration-Interconnection, Islamic Education